The Effectiveness Of The School Literacy Movement (GLS) Program In Increasing Students' Interest In Reading In Subjects PAI Di SMA Negeri 2 Rujukan Lubuklinggau - Mawardi, Anjali Fitrah; Fitriyani, Fitriyani; Helandri, Joni (Edification Journal : Pendidikan Agama Islam, 2025)
The background to this research is that the School Literacy Movement (GLS) is a program that aims to increase reading interest and reading skills as well as writing skills. Its implementation at SMA Negeri 2 Lubuklinggau has reached the development stage. The problem in this research is the lack of interest in reading and the lack of awareness among students about how important reading is, especially in PAI subjects. This type of research is descriptive qualitative research. The subjects of this research were the deputy principal for curriculum, PAI teachers, school literacy ambassadors, and 11 students as samples taken from each class. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this research show that the effectiveness of the GLS program is very influential in increasing students' reading interest in PAI subjects. With the 15 minute reading habit program and writing activities, students increase awareness of how important reading is. However, some students also expect explanations from the teacher to strengthen what the students have read. Students' interest in reading is also aroused by encouragement from technology which increases students' curiosity. The effectiveness of this program also has a positive effect on students' ethics and manners, by reading they become aware of Islamic teachings about ethics and manners so that they can immediately apply them in their daily lives. In this case, literacy ambassadors also play an active role in providing education to students about the importance of reading.